Effect of Physical Activity on Plasma PCSK9 in Subjects With High Risk for Type 2 Diabetes - Mäkelä, Kari Antero; Leppäluoto, Juhani; Jokelainen, Jari; Jämsä, Timo; Keinänen-Kiukaanniemi, Sirkka; Herzig, Karl-Heinz (Frontiers in Physiology, 2019)
Background Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a liver serine protease regulating LDL cholesterol metabolism. PCSK9 binds to LDL receptors and guides them to lysosomes for degradation, thus increasing the amount of circulating LDL cholesterol. The aim of the study was to investigate associations between physical activity and plasma PCSK9 in subjects with high risk for type 2 diabetes (T2D). Methods Sixty-eight subjects from both genders with a high risk for T2D were included to a randomized controlled trial with a 3-month physical activity intervention. Physical activity intensities and frequencies were monitored throughout the intervention using a hip worn portable accelerometer. The plasma was collected before and after intervention for analysis of PCSK9 and cardiovascular biomarkers. Results Plasma PCSK9 did not relate to physical activity although number of steps were 46% higher in the intervention group than in the control group (p < 0.029). Total cholesterol was positively correlated with plasma PCSK9 (R = 0.320, p = 0.008), while maximal oxygen uptake was negatively associated (R = -0.252, p = 0.044). After the physical activity intervention PCSK9 levels were even stronger inversely associated with maximal oxygen uptake (R = -0.410, p = 0.0008) and positively correlated with HDL cholesterol (R = 0.264, p = 0.030). Interestingly, plasma PCSK9 levels were higher in the beginning than at the end of the study. Conclusion The low physical activity that our subjects with high risk for T2D could perform did not influence plasma PCSK9 levels. Intervention with higher physical activities might be more effective in influencing PCSK9 levels.